Horticultural Farmer's Perceptions and Adaptations to Climate Change in East Java, Indonesia - Atasa, Dita; Widayanti, Sri; Laily, Dona Wahyuning; Toiba, Hery (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2024)
The agricultural sector highly vulnerable to the risks and impacts of global climate change. Horticultural farmers in East Java have experienced climate change, which is marked by a decrease in the level of productivity produced in recent years. This study aims to determine how farmers' perceptions of climate change and adaptation strategies are carried out. Data were collected through direct survey to horticultural farmers in Malang and Kediri Regencies, East Java. Data analysis was carried out descriptively, by describing the data that had been collected regarding the perception and adaptation of farmers. The results of the study shows that farmers have a high perception of climate change. Farmers' strategies in dealing with climate change include the adaptation by changing cropping patterns, changing plant varieties, changing plant types, changing fertilizer inputs, doing irrigation, and increasing knowledge and skills about agriculture.